Functional feeding groups of Chironomidae (Diptera: Nematocera) and their spatial variation in an intermittent hill stream (Ventana Stream, Buenos Aires, Argentina) - Ocon, Carolina Silvia (2023)
The feeding habits of Chironomidae in hill streams in the pampean region have not been described. In this study, we analyzed the gut contents of this insect family with an aim at establishing their diet in an intermittent stream in the Ventania-Hill system. We sampled three sites with different habitat characteristics (i. e., altitude, substrate type, and current velocity). Of the total of nine taxa were recorded, the only one present at all sites was Corynoneura sp. 1. The food items found were detritus, diatoms, filamentous chlorophytes, euglenophytes, vascular plants, fungi, and animal remains. Most of the taxa could be classified as gathering collectors, with those having a higher proportion of detritus in the gut contents although the guts of Pentaneura nr. cinerea, Cricotopus sp. 1, and Onconeura analiae included high proportions of animal remains. No differences in the feeding habits were attributable to the location in the stream. This research contributes to our understanding of the trophic habits of Chironomidae in an intermittent hill stream system of South America.